Claudin-1 is linked to presence of implants and micropapillary pattern in serous borderline epithelial tumours of the ovary. Issue 12 (31st August 2018) - El-Balat, Ahmed; Schmeil, Iryna; Gasimli, Khayal; Sänger, Nicole; Karn, Thomas; Ahr, Andre; Becker, Sven; Arsenic, Ruza; Holtrich, Uwe; Engels, Knut
Abstract : Aims: Expression of Claudin-1 has been associated with prognosis in several cancers. Here we investigated the expression pattern of Claudin-1 in borderline tumours of the ovary (BOT). Methods: We analysed a cohort of 114 cases of borderline tumour (BOT). Claudin-1 expression was studied by immunohistochemistry using a polyclonal antibody and was compared with clinical and histopathological characteristics. Results: Strong Claudin-1 expression was found in 30 cases (26.3%) independent of histological subtype. Expression was significantly less frequent in International Federation of Gynecology and Obstetrics (FIGO) stage I (p= 0.045), while the presence of microinvasion did not correlate with Claudin-1 expression. In contrast, we detected a highly significant association of Claudin-1 expression with the presence of peritoneal implants (p=0.003) and micropapillary pattern (p=0.047), which are features exclusively seen in serous BOT. Moreover, when we restricted our analysis to the subtype of serous BOT, the association of Claudin-1 expression with peritoneal implants (p<0.001) and micropapillary pattern (p =0.003) remained highly significant. Conclusions: In conclusion, Claudin-1 expression is associated with the presence of peritoneal implants and micropapillary pattern, which have been shown to be associated with poor prognosis. We speculate that overexpression of Claudin-1 might be linked to the mitogen-activated protein kinase pathway activation in BOT and suggest further studies to define its prognostic and potential therapeutic value.